Pemanfaatan Instagram @whatisupindonesia dalam Membangun Kesadaran Politik Generasi Z - Gracia Zephaniah; Suparman Suparman; Amiruddin Saleh; Rici Tri Harpin Pranata (CV. ULIL ALBAB CORP, 2025)
Development of digital technology has significantly changed how young generations, especially generation Z, access political information. This study aims to analyze utilization of the Instagram account @whatisupindonesia as a means to enhance political awareness among generation Z. Methods used in this research include content analysis and interviews with relevant informants. Results indicate that content posted by this account successfully captures attention of young audiences and encourages them to participate more actively in political discussions. Use of visual elements and a casual language style in presenting political information makes complex issues easier to understand. Research concludes that social media, particularly Instagram, can serve as an effective tool for building political awareness among generation Z. Involvement of generation Z in broader political processes can be improved through engaging and relevant content strategies. It is essential for social media account managers to continuously develop innovative approaches to convey political information to generation Z in the future.